2019
DOI: 10.2147/ott.s191609
|View full text |Cite
|
Sign up to set email alerts
|

<p>Upregulation of STC2 in colorectal cancer and its clinicopathological significance</p>

Abstract: Background Stanniocalcin 2 (STC2) is a glycoprotein hormone involved in many biological processes and a secretory protein that regulates malignant tumor progression. The aim of the present study was to further explore the clinicopathological significance and prognostic role of STC2 in colorectal cancer (CRC). Methods In this study, STC2 expression was first investigated in Gene Expression Omnibus and The Cancer Genome Atlas, and then validated with the data from our med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 43 publications
3
38
1
Order By: Relevance
“…Among them, STC2 can regulate glucose homeostasis [ 45 ]. Studies have found that high expression of STC2 is associated with tumor invasion, metastasis, and poor prognosis [ 46 ]. STC1 uncouples the process of oxidative phosphorylation via an increased expression of mitochondrial UCP2 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, STC2 can regulate glucose homeostasis [ 45 ]. Studies have found that high expression of STC2 is associated with tumor invasion, metastasis, and poor prognosis [ 46 ]. STC1 uncouples the process of oxidative phosphorylation via an increased expression of mitochondrial UCP2 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling pathway activation, a signal for CRC carcinogenesis, has recently been reported to cause decreased level of SLC10A2 [45]. STC2 has recently been reported as an independent prognostic biomarker, whose expression is related to colon cancer progression [46]. The overexpression of ESM1 in serum of CRC patients has been revealed Ji et al [47].…”
Section: Discussionmentioning
confidence: 99%
“…Role of STC2 in human cancers has been studied from two different perspectives namely expression of STC2 in specific cancer models and cell lines, and STC2's function in cell growth, differentiation and apoptosis. Several reports suggest elevated expression of STC2 in human hepatocellular carcinoma, neuroblastoma, breast cancer, colorectal cancer, renal cell carcinoma, esophageal squamous cell cancer, and prostate cancer (41,(64)(65)(66)(67)(68)(69). Additionally, expression of STC2 was correlated with tumor invasion, metastasis and size in gastric cancers and hepatocellular carcinoma (70).…”
Section: Tumor Biologymentioning
confidence: 98%